SmFeTaO Photocatalyst for Degradation of Indigo Carmine Dye under Solar Light Irradiation - Torres Martínez, Leticia Myriam; Ruiz Gómez, Miguel A.; Figueroa Torres, Mayra Zyzlila; Juárez Ramírez, Isaías; Moctezuma, Edgar (Hindawi Publishing Corporation, 2012)
This paper is focused to study Sm2FeTaO7 pyrochlore-type compound as solar photocatalyst for the degradation of indigo carmine dye in aqueous solution. Sm2FeTaO7 was synthesized by using conventional solid state reaction and sol-gel method. X-ray diffraction results indicated that Sm2FeTaO7 exhibit a monoclinic crystal structure. By scanning electron microscopy analysis, it was observed that sol-gel material presents particle size of around 150 nm. The specific surface area and energy bandgap values were 12 m2 g−1 and 2.0 eV, respectively. The photocatalytic results showed that indigo carmine molecule can be degraded under solar light irradiation using the synthesized materials, sol-gel photocatalyst was 8 times more active than solid state. On the other hand, when Sm2FeTaO7 was impregnated with CuO as cocatalyst the photocatalytic activity was increased because CuO acts as electron trap decreasing electron-hole pair recombination rates.